OPEN EDUCATION AN IMPETUS FOR 21ST CENTURY EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 14 November 2016 – The university needs to implement the open education programme in line with the flexible education system to fulfil the demands of skilled workforce in the future, while being able to adapt to current conditions and not merely abiding by requirements set by the Malaysian Ministry of Education.